Effectiveness of an on-body lifting aid (HAL® for care support) to reduce lower back muscle activity during repetitive lifting tasks. (May 2019) - von Glinski, Alexander; Yilmaz, Emre; Mrotzek, Silvia; Marek, Eike; Jettkant, Birger; Brinkemper, Alexis; Fisahn, Christian; Schildhauer, Thomas A.; Geßmann, Jan
Highlights: We confirmed the feasibility of using sEMG analysis to study a biosignal triggered Exoskeleton. Using a voluntary controlled lifting aid (HAL) significantly reduced lumbar muscle activity. No influence on the perceived exertion of the subjects. No influence on the cardiovascular parameters. Abstract: The Hybrid Assistive Limb Lumbar Type (HAL) is an active exoskeleton that provides motion according to the wearer's voluntary drive. It was developed to support back muscles during repetitive lifting tasks. The purpose of this paper was to determine if the myoelectric activity of the back muscles is reduced or altered when using the HAL and to investigate a possible influence of its use on the cardiovascular system. Fourteen healthy young men without lower back pain underwent a freestyle, symmetrical-lifting protocol. Participants lifted a 17.05 kg handled-box for 10 min. with and without HAL support. Surface electromyography (sEMG) signals were recorded at thoracic (TES) and lumbar erector spinae (LES) and quadriceps femoris (QF). Heart rate was recorded from electrocardiogram. The subjects rated their level of physical exertion using the Borg Rating of Perceived Exertion (BORG) scale. Additionally they commented on sites of discomfort, perceptions of force, and loss of range of motion. The root mean square and integrated sEMG value was significantly reduced at the LES and TES. Heart rate variability output variables did not show any significant difference. The BORG-Scale showed no difference, with a mean score of 2.5. The HAL decreased the magnitude and onset of muscle activity and force in the lower back in a repetitive lifting task. Reduction of the muscle force and activity required during the lifting process is meaningful regarding lower back pain prevention, and the HAL may contribute to reducing the incidence of lower back pain in the working population.